Incarcerated Lumbar Hernia Complicated by Retroperitoneal Pseudoaneurysm 50 Years after Resection and Radiation Therapy of a Sarcoma - Oluwatobi Onafowokan; Dabanjan Bandyopadhyay; Dale Johnson; Hugo J. R. Bonatti (Case Reports in Surgery)
Background. Lumbar hernias are rare abdominal hernias. Surgery is the only treatment option but remains challenging. Posterior incisional hernias are even rarer especially with incarceration of intra-abdominal contents. Case Presentation. A 68-year old female presented with a 3-day history of worsening acute abdominal pain and distension, with multiple episodes of emesis. A CT scan indicated a large incarcerated posterolateral abdominal hernia. The patient had a history of resection of a sarcoma on her back as a child and also received chemotherapy and radiation. During emergency laparoscopy, a hemorrhagic small bowel segment incarcerated in the hernia was reduced and resected, and the distended small bowel was decompressed. An elective hernia repair was scheduled. After temporary clinical improvement, the patient again developed abdominal pain, distention, and emesis. During emergency laparotomy, a large hematoma in the right flank was found and partially evacuated. The right colon was mobilized out of the hernia and the duodenum was kocherized. A 20×20 cm BIO-A mesh was placed on top of the Gerota fascia and cranially tucked under liver segment VI. Anteriorly, the mesh was fixated with absorbable tacks. The duodenum and colon were placed into the mesh pocket. A postoperative CT scan identified a 2 cm pseudoaneurysm of a side branch of a lumbar artery, and the bleeding source was embolized. The postoperative course was complicated by Clostridium difficile-associated colitis, but ultimately, the patient recovered fully. At 6-month follow-up, there was no evidence for a recurrent hernia. Discussion. There is a paucity of literature concerning lumbar incisional hernias. Repair with bioabsorbable mesh seems feasible, but longer follow-up is necessary as the mesh was placed in an unusual fashion due to the retroperitoneal hematoma. The exact cause of the hemorrhage is unclear and may have been caused during the initial incarceration, during surgery, or may be a late complication of her previous radiation.